Identifying climate information services users and their needs in sub-Saharan Africa: A learning agenda - Carr, Edward R.; Goble, Rob; Rosko, Helen M.; Vaughan, Catherine; Hansen, James (United States Agency for International Development, 2018)
In recent years, climate information services (CIS) have been integrated into development agendas as means of achieving development goals in a variable and changing climate, shifting the emphasis of CIS from the packaging of existing climate analysis toward addressing pressing social concerns. Today, the starting point for making an effective CIS is attention to the potential users of the service and their particular needs. The design and management of effective services requires the identification the intended users of climate information, work to establish how climate information could be useful in the context of their lives, and plans to deliver credible, salient, and legitimate climate information that meets one or more of their needs. However, the practical experience of identifying these users and needs remains uneven across the field. Different projects have taken different approaches and made different assumptions, often with limited testing either. There are gaps in our knowledge related to who can best be helped by climate information, what climate information meets user needs, the most productive means by which to identify these populations and their needs, and how to generalize knowledge about users and needs. This paper presents a learning agenda for acquiring further knowledge about the users of CIS and their needs. As a learning agenda, it reviews the state of current knowledge on this subject. However, it goes beyond a review to focus on what we do not know, and to argue for what is needed to answer or fill those gaps in knowledge. Further, it prioritizes these gaps, organizing a process of inquiry that builds upon itself to inform both CIS research and practice. Thus, this paper speaks to current “good practices” in CIS design, management, and evaluation, while pointing the way to better practices in the future.